Eccrine carcinoma : a rare cutaneous neoplasm - Idrissi Serhrouchni Karima; Harmouch Taoufiq; Chbani Laila; El Fatemi Hind; Sekal Mohammed; Hammas Nawal; Soughi Meriem; Benchat Loubna; Amarti Afaf (BMC, 2013)
Abstract Eccrine carcinoma is an extremely rare malignancy of the skin with few well documented cases reported in the literature. It is frequently found on the lower extremities, and it equally affects both sexes in the sixth and seventh decade. In our case, we present a 46- year-old female with a recurring exophytic tumor on the right lower extremity, without local extension. The initial tumor was biopsied, excised and diagnosed as an eccrine carcinoma. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/3568051328673318.